2011
DOI: 10.1590/s0100-83582011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da intoxicação de cultivares de cana-de-açúcar e I. grandifolia ao amicarbazone

Abstract: O objetivo deste trabalho foi avaliar a intoxicação de planta daninha e cultivares de cana-de-açúcar ao amicarbazone. Para isso, utilizou-se Ipomoea grandifolia como planta daninha representante e os cultivares de cana-de-açúcar PO8862, SP80 3280 e RB83 5486, caracterizados como sensível, intermediário e tolerante aos herbicidas, respectivamente. Foi verificado o consumo de água e quantificada a concentração do amicarbazone em seiva de xilema dos três cultivares de cana-de-açúcar e de I. grandifolia por meio d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The use of amicarbazone in the culture of sugarcane can present high selectivity so that more cultivars tolerant to this molecule have a lower absorption of the herbicide when compared to sensitive cultivars, which absorb more of it (Araldi et al, 2011).…”
Section: Greenhouse Experimentsmentioning
confidence: 99%
“…The use of amicarbazone in the culture of sugarcane can present high selectivity so that more cultivars tolerant to this molecule have a lower absorption of the herbicide when compared to sensitive cultivars, which absorb more of it (Araldi et al, 2011).…”
Section: Greenhouse Experimentsmentioning
confidence: 99%
“…The cultivar of sugarcane experiments 2 and 3 was RB835054; experiments 4 and 5, RB867515; and experiment 1, RB855453. Araldi et al (2011) found differential susceptibility of sugarcane cultivars PO8862, SP803280 and RB835486 to herbicide amicarbazone, justified, possibly by differential absorption of the herbicide between cultivars. Moreover, regardless of genetic material, the mesotrione and mesotrione + atrazine treatments did not cause visual symptoms of phytotoxicity on sugarcane.…”
Section: Resultsmentioning
confidence: 86%
“…Araldi et al (2011) salientaram que as cultivares de uma mesma cultura, ao absorverem maior quantidade de herbicidas, podem apresentar menor tolerância.…”
Section: Introductionunclassified